DEMPSEY, Lorcan and VARNUM, Kenneth J. The Network Reshapes the Library: Lorcan Dempsey on libraries, services and networks. London: Facet. 2014. 320 pages. ISBN-13 978 1783300419. £44.95. (2015) - O'Beirne, Rónán
No abstract available